1997
DOI: 10.1002/cjce.5450750413
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme mass transfer coefficient in aqueous two‐phase systems: Modified spray extraction columns

Abstract: The fractional dispersed phase hold-up and mass transfer coefficients were measured in modified spray columns of 50 mm i.d. using an aqueous two phase system of polyethylene glycol (PEG 4000)-sodium sulphate-buffer. The mass transfer coefficients were measured for amyloglucosidase and pgalactosidase. Both co-current and countercurrent modes of operation were investigated.The dispersed phase hold-up ( g o ) and the dispersed phase and the continuous phase mass transfer coefficients (kDa, k p ) increased with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…Among the techniques used for protein recovery and purification, liquid-liquid extraction using aqueous two-phase systems (ATPS) offers the advantages of gentle environment, favorable processing time and easy scale-up (Albertsson, 1986;Oliveira et al, 2002). Methods of conventional extraction, such as spray column, can be conveniently applied to aqueous two-phase systems (Sawant and Sikdar, 1990;Jafarabad et al, 1992a and b;Pawar et al, 1997). Another tool that has been recently successfully applied for liquid-liquid extraction with aqueous two-phase systems is the perforated rotating disc contactor (PRDC).…”
Section: Introductionmentioning
confidence: 99%
“…Among the techniques used for protein recovery and purification, liquid-liquid extraction using aqueous two-phase systems (ATPS) offers the advantages of gentle environment, favorable processing time and easy scale-up (Albertsson, 1986;Oliveira et al, 2002). Methods of conventional extraction, such as spray column, can be conveniently applied to aqueous two-phase systems (Sawant and Sikdar, 1990;Jafarabad et al, 1992a and b;Pawar et al, 1997). Another tool that has been recently successfully applied for liquid-liquid extraction with aqueous two-phase systems is the perforated rotating disc contactor (PRDC).…”
Section: Introductionmentioning
confidence: 99%
“…A similar trend of increase in holdup with dispersed phase velocity was reported by Sarubbo et al [12] in PRDC for the extraction of BSA using PEG 4000 -cashew-nut tree gum system. Pawar et al [2] and Jafarabad et al [1] have also reported the same for the extraction of BSA and for the simultaneous extraction of amyloglucodiase and β-galactosidase in spray column using PEG 4000 -sodium sulphate/potassium phosphate systems, respectively. Since, the increase of dispersed phase velocity increases the kinetic and buoyancy forces acting on the droplets and eventually results in the formation of smaller and more PEG droplets [26] .…”
Section: Effect Of Dispersed Phase Velocity (U D )mentioning
confidence: 88%
“…Continuous counter-current column extractors have more than one theoretical stage are preferred over mixer/agitated vessel -centrifuge due to reasonably less capital and operational cost and possibility to obtain higher purity of partitioned biomolecules [1]. Scale-up and continuous counter-current ATPE has been demonstrated in the conventional liquid-liquid extractors such as spray columns [1][2][3], and packed columns [4]. With this understanding, Biazus et al [5] introduced a micro extraction column for the ATPE of α and β -amylases from Zea mays malt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods of conventional extraction such as Spray columns can be conveniently applied to aqueous two-phase systems (Jafarabad et al, 1992;Pawar et al, 1993;Sawant et al, 1990). Perforated rotating disc contactors were used with aqueous biphasic systems (Porto et al, 1997;2000).…”
Section: Introductionmentioning
confidence: 99%